Psychological Factors and Alcohol Use in Problematic Mobile Phone Use in the Spanish Population - De-Sola, José; Talledo, Hernán; Rubio, Gabriel; de Fonseca, Fernando Rodríguez (Frontiers in Psychiatry, 2017)
This research aims to study the existing relationships among the factors of state anxiety, depression, impulsivity and alcohol consumption regarding problematic mobile phone use, as assessed by the Mobile Phone Problem Use Scale (MPPUS). The study was conducted among 1.126 participants recruited among the general Spanish population, aged 16 to 65 years, by assessing the predictive value of these variables regarding this problematic use. In general terms, the results show that this problematic use is mainly related to state anxiety and impulsivity, through the dimensions of Positive and Negative Urgency. Considering its predictive value, multiple regression analysis reveals that state anxiety, Positive and Negative Urgency, and alcohol consumption may predict problematic mobile phone use, ruling out the influence of depression.